(untitled) (Construction Economics and Building, 2020)
A Delphi study using twenty-three project practitioners over six rounds is aimed to identify significant problems in project management, arising from the nature of projects other than those readily identifiable in a literature review. The study goes on to identify project managers’ behaviours which are recognised as having successful impacts on the delivery of projects. A Relative Importance Index for the problems and behaviours resulting from the issues identified in the study is calculated. This study continues by reporting the views of practitioners involved in the management of large projects on the everyday problems they experience in managing projects, problems that are not adequately addressed in current project management texts concerning the nature of projects. Five additional problems, not generally discussed in the literature, were identified together with seven interpersonal skills and behaviours that are major contributors to increasing the likelihood of a successful project delivery.